Critical thinking in school psychology: Epistemological aspects - Meira, Marisa Eugenia Melillo [UNESP] (My University, 2016)
This chapter we aim at contributing hope to the understanding and analysis of critical thinking the main epistemological foundations in the field of School Psychology. For this purpose we start from the premise that a critical conception of School Psychology must be based on criticisms of Education and Psychology conceptions. Therefore, some core elements of dialectical historical materialism that support critical thinking, such as dialectical reflection, critical knowledge, denunciation of human degradation and defending the dignity of life, justice and freedom for all men, as well as conception of criticism as social transformation are explicit here. For this reasons we approach discuss contributions from Historical-Critical Pedagogy for to the critical thinking in Education, considering that a critical conception of Education forms one of the bases for the proposition of setting purposes and critical practices in the field of School Psychology. Further on we discuss contributions of Historical-Cultural Psychology for the basis of critical thinking in psychology, so we can focus more specifically on the contributions of the Historical-Critical Pedagogy and Historical-Cultural Psychology for critical thinking in the field of School Psychology. Finally, based on the assumptions of dialectical historical materialism, we emphasizes the importance of Psychology and the school psychologist’s ethical and political commitment to the humanization of individuals, human emancipation and the struggle for social transformation and for the quality of education for all.
Keywords: Critical psychology; Historical-critical pedagogy; Historical-cultural psychology; School psychology